Impact of social problem-solving training on critical thinking and decision making of nursing students - Soleiman Ahmady; Sara Shahbazi (BMC, 2020)
Abstract Background The complex health system and challenging patient care environment require experienced nurses, especially those with high cognitive skills such as problem-solving, decision- making and critical thinking. Therefore, this study investigated the impact of social problem-solving training on nursing students' critical thinking and decision-making. Methods This study was quasi-experimental research and pre-test and post-test design and performed on 40 undergraduate/four-year students of nursing in Borujen Nursing School/Iran that was randomly divided into 2 groups; experimental (n = 20) and control (n = 20). Then, a social problem-solving course was held for the experimental group. A demographic questionnaire, social problem-solving inventory-revised, California critical thinking test, and decision-making questionnaire was used to collect the information. The reliability and validity of all of them were confirmed. Data analysis was performed using SPSS software and independent sampled T-test, paired T-test, square chi, and Pearson correlation coefficient. Results The finding indicated that the social problem-solving course positively affected the student' social problem-solving and decision-making and critical thinking skills after the instructional course in the experimental group (P < 0.05), but this result was not observed in the control group (P > 0.05). Conclusions The results showed that structured social problem-solving training could improve cognitive problem-solving, critical thinking, and decision-making skills. Considering this result, nursing education should be presented using new strategies and creative and different ways from traditional education methods. Cognitive skills training should be integrated in the nursing curriculum. Therefore, training cognitive skills such as problem- solving to nursing students is recommended.